The correlation analysis between logistics performance and financial performance of Thai industry - Suphawadi Chakkham (2019)
© 2019 ACM. The main purpose of this paper is to analyze correlation and explore the logistics scorecard factors that are influencing the implementation of financial performance in the Thai industry. The data collected from the logistics scorecard appraisal forms of 254 sectors in Thailand. Factor Analysis (Principal component analysis: PCA) Technique was applied to the construct validity of factors to extract factors of logistics scorecard indicators from all 23 items. The factor scores of the generated elements were analyzed by using correlation techniques and regression analysis with dependent variables as selected financial ratios. The results of the paper demonstrated that three organizational factors were Organizational Management and development factor, Service and Responsiveness factor and Information Management factor. Also, the Information Management factor influenced Receivable Turnover Ratio, Assets to Equity ratio and Debt to Equity ratio at a significant level.